Chlorine evolution reaction composite electrode material and preparation method and application thereof
By manufacturing the nitrogen-oxygen double defect layer anchoring active metal on the surface of the titanium matrix, a chlorine-precipitation reaction composite electrode material was prepared, which solved the problems of high precious metal content, high cost, low activity and poor stability of the existing electrode materials, and achieved low cost, high activity and high stability of the electrode materials.
Patent Information
- Application Number
- CN202510178432.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing chlorine-elimination reaction electrode materials have problems such as high precious metal content, high production cost, low catalytic activity and poor stability, and it is difficult to be used stably in the harsh electrolytic environment of the chlor-alkali industry for a long time.
The titanium matrix is processed by treating a mixed solution of nitrogen source and polyformaldehyde to form a nitrogen-oxygen double-deficient layer, anchoring the electrode deposited active metal, and finally calcining under an oxygen environment to prepare a chlorine-eliminate reaction composite electrode material.
Maintaining the reactive activity and stability of the electrode under extremely low precious metal content avoids the need to form a uniform and dense active metal layer, reduces production costs, and improves the service life of the electrode.
Smart Images

Figure CN119640308A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of equipment used in electrolytic processes for producing compounds, and in particular to a chlorine evolution reaction composite electrode material, a preparation method and an application thereof. Background Art
[0002] As an important chemical raw material, chlorine has important applications in polymer synthesis, wastewater treatment, metallurgical industry, and synthesis of disinfectants. The output of chlorine is 70-100 million tons per year, of which about 90% comes from the chlor-alkali industry. As the main source of chlorine, the production and development of the chlor-alkali industry is particularly important. In the chlor-alkali industry, researchers have designed and synthesized various types of electrode materials and used them as positive electrodes in the chlorine evolution reaction (CRE). Among electrode materials, there is a solution of using cheap metals to make electrode materials. Although its production cost can be controlled, the electrode material often has the defects of being extremely unstable and having low catalytic activity, and it is difficult to be used in the harsh electrolysis environment of the chlor-alkali industry for a long time and stably. Therefore, the electrode material currently used in the chlorine evolution reaction is mainly a dimensionally stable anode (DSA). The preparation method of DSA electrode is usually to deposit precious metals such as ruthenium or iridium on a titanium plate substrate by electroplating or chemical reaction to form an anode with an active coating.
[0003] For example, the Chinese invention patent with publication number CN103439385A discloses a DSA electrode, a manufacturing method, and an ammonia nitrogen detection device and method based on the DSA electrode. The DSA electrode includes an electrode substrate, which is a titanium plate; an electrode intermediate layer and an electrode active layer are arranged in sequence on the outer surface of the electrode substrate; wherein the material of the electrode intermediate layer is SnO2-Sb2O x , the material of the electrode active layer is TiO2-RuO2-IrO2-F. The invention adopts coating, drying or sintering to prepare the electrode intermediate layer and the electrode active layer in sequence. For example, the Chinese invention patent with publication number CN113816468A provides a DSA electrode and its preparation method and application. The composition of the DSA electrode includes a titanium substrate and a metal oxide coating coating the titanium substrate, the metal oxide coating is composed of metal oxide nanosheets grown in situ on the surface of the titanium substrate, and the metal oxide nanosheets are composed of tin dioxide and at least one of antimony pentoxide, ruthenium dioxide and manganese dioxide. The preparation method of the DSA electrode of the invention includes the following steps: 1) preparing an organic acid solution; 2) preparing a precursor solution; 3) adding a titanium sheet to the precursor solution, performing a hydrothermal reaction or a solvothermal reaction, and then taking out the titanium sheet for calcination to obtain a DSA electrode.
[0004] For DAS electrode active coatings prepared by chemical reaction, due to the influence of chemical reaction kinetics, the reaction process is accompanied by side reactions, and the utilization rate of the substrate is limited; in order to obtain the target use effect, it is usually necessary to use more substrate than the chemical reaction amount during its preparation process. In contrast, the electroplating process can complete the preparation of the coating on the titanium substrate with high current efficiency, but the electrode material needs to have good chemical and thermal stability and reactivity to maintain its structure and performance. In order to ensure the uniform performance of the electrode and avoid coating peeling, the metal elements need to be evenly distributed on the titanium substrate in a certain way and form a strong bond with the substrate. This usually means that a thicker coating is required to form sufficient active sites and ensure the continuity and mechanical strength of the coating, thereby increasing the amount of metal elements used.
[0005] At present, DSA electrodes have the advantages of high catalytic activity and good stability. However, the high content of precious metals in such electrodes greatly increases the production cost and hinders the further development of the chlor-alkali industry. Therefore, on the basis of meeting application requirements, designing a composite electrode material for chlorine evolution reaction with lower precious metal content and good bonding with the substrate has positive significance for the development of the chlor-alkali industry. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for preparing a chlorine evolution reaction composite electrode material with simple process and low production cost is provided, comprising the following steps: Step (1), mixing a nitrogen source, polyoxymethylene and an organic solvent to prepare a mixed solution; Step (2), immersing the titanium substrate in the mixed solution and performing heat treatment, and obtaining a coated titanium substrate after completion; Step (3), calcining the coated titanium substrate under an inert atmosphere to obtain a defective electrode material; Step (4), depositing active metal in the defective electrode material by electrodeposition to obtain a coating electrode material; Step (5), the coated electrode material is calcined in an oxygen atmosphere to obtain a chlorine evolution reaction composite electrode material.
[0007] Preferably, in step (1), the nitrogen source includes at least one of melamine, urea and amino acid.
[0008] The organic solvent plays a role in promoting the dispersion of substances and creating a suitable environment for the reaction during the preparation, and is chemically inert relative to the raw materials. Those skilled in the art can use a suitable solvent type according to the physical and chemical properties of the nitrogen source and polyoxymethylene and actual conditions. For example, solvents such as dimethyl sulfoxide, acetonitrile, and N,N-dimethylacetamide are particularly suitable solvents for this step.
[0009] Preferably, in step (1), the organic solvent includes at least one of dimethyl sulfoxide, acetonitrile and N,N-dimethylacetamide.
[0010] Adjusting the molar ratio of nitrogen source to polyoxymethylene is beneficial to form the targeted nitrogen-oxygen double defects in a more efficient manner and optimize the binding properties of active metals in electrode materials.
[0011] Preferably, in step (1), the molar ratio of the nitrogen source to polyoxymethylene is 1:2-5; and the concentration of the nitrogen source in the mixed solution is 0.05-3 mol / L.
[0012] The heat treatment step is simple and has good applicability, and can be completed on the surface of a titanium substrate in a common form in the art (such as a flat plate, mesh, tubular, rod or other customized shapes, homemade or commercial, etc.).
[0013] Preferably, in step (2), the heat treatment temperature is 100-200°C and the heat treatment time is 24-48 h.
[0014] Preferably, in step (3), the calcination temperature is 800-1000°C, and the calcination time is 1-3 h.
[0015] Preferably, in step (4), the active metal includes at least one of ruthenium, iridium and platinum.
[0016] Preferably, in step (4), the electrodeposition method is as follows: using an electrolyte containing a soluble active metal salt as a deposition liquid; immersing the defective electrode material in the deposition liquid for electrodeposition to obtain a coating electrode material.
[0017] Cyclic voltammetry electrodeposition is applicable to a variety of conductive substrates, including metals, semiconductors, and conductive polymers, and can be efficiently used to prepare a variety of composite materials. Cyclic voltammetry electrodeposition allows the deposition process to be controlled by adjusting the potential scan rate and the number of cycles, thereby precisely controlling the composition, structure, and morphology of the material. Compared with other physical vapor deposition or liquid phase chemical synthesis methods, it does not require expensive equipment or complex precursor processing steps, is easy to scale up to industrial production, and is suitable for large-scale synthesis applications. Therefore, it is highly cost-effective both at the laboratory scale and in industrial production.
[0018] Further preferably, the electrodeposition adopts cyclic voltammetry electrodeposition method.
[0019] In actual production, considering factors such as raw material cost, source and waste treatment, soluble active metal salts and water-based electrolytes have significant advantages in the above aspects. In addition, ruthenium salts in active metal salts can show excellent solubility and ionization ability in water. Water, as a good solvent for active metal salts, can also better achieve the effect of electrodeposition.
[0020] Further preferably, the soluble active metal salt includes at least one of ruthenium chloride, ruthenium nitrate and ruthenium oxalate; in the deposition liquid, the solvent is water, and the concentration of the soluble active metal salt is 0.1-0.3 g / L.
[0021] Preferably, in step (4), the current density of the electrodeposition is 10-50 mA / cm 2 , the electrodeposition time is 200-400 s.
[0022] Preferably, in step (5), the calcination temperature is 300-500°C and the calcination time is 1-4 h.
[0023] In the second aspect of the present invention, a chlorine evolution reaction composite electrode material with good stability and reaction activity and low precious metal content is provided, which is prepared by the method provided in the first aspect of the present invention.
[0024] In the third aspect of the present invention, there is provided an application of the composite electrode material for chlorine evolution reaction according to the second aspect of the present invention, specifically, as an electrode material for preparing an electrode for chlorine evolution reaction.
[0025] At present, a variety of electrode materials have been designed and synthesized in the field for use as positive electrodes in chlorine evolution reactions. Among them, although the production cost of electrode materials made of cheap metals can be controlled, the electrode materials are extremely unstable and have low catalytic activity, making it difficult to exist for a long time in the harsh electrolysis environment of the chlor-alkali industry. If precious metals (i.e., active metals) are used to make electrode materials, in order to ensure good catalytic activity, etc., the content of precious metals needs to be increased, and the cost is relatively high. Therefore, in the design and development stage, the technical difficulties that the present invention needs to overcome are mainly to reduce the amount of active metals used while taking into account the application requirements of high catalytic activity and good stability.
[0026] The inventors have found that the main factors affecting the activity and stability of electrode materials include the content of precious metals in the titanium substrate; when the content is reduced, it means that the precious metals are difficult to maintain the structure and performance of the coating. Therefore, the design concept of the present invention is to treat the titanium substrate with a mixed solution containing a nitrogen source and polyoxymethylene, first coat a gel layer on its surface, then calcine in an oxygen-free environment, anchor the electrodeposited active metal by creating nitrogen and oxygen double defects on the surface of the titanium substrate, and finally calcine in an aerobic environment to prepare a chlorine evolution reaction composite electrode material. In this way, the reaction activity of the electrode can be maintained at an extremely low precious metal content. Due to the good adhesion and stability of the active metal, there is no need to form a uniform, dense, and continuous active metal layer, which overcomes the defect of large active metal usage in existing electrodes.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for preparing a chlorine evolution reaction composite electrode material, which has a simple process, low production cost and is suitable for industrial-scale production.
[0028] The invention provides a chlorine evolution reaction composite electrode material, which has the advantages of low precious metal content, good stability and reaction activity.
[0029] The present invention provides an application of a chlorine evolution reaction composite electrode material, which has good application prospects as an electrode material in chlorine evolution reaction by electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The microscopic morphology characterization results of the chlorine evolution reaction composite electrode material prepared in Example 1, wherein (a) is a scanning electron microscope (SEM) image of the chlorine evolution reaction composite electrode material; (b) is a transmission electron microscope (TEM) image of the chlorine evolution reaction composite electrode material; Figure 2 The linear sweep voltammetry (LSV) test results of the chlorine evolution reaction composite electrode materials prepared in Examples 1-4, the composite electrode materials prepared in Comparative Example 1, and the commercial DSA electrode, wherein (a) is the overall curve of the linear sweep voltammetry test results and its LSV curve at 0-50 mA / cm 2 Schematic diagram of the cut-off fragment under the current density range; (b) is a partial enlarged diagram of the schematic diagram of the cut-off fragment in (a); Figure 3 This is the chronoamperometry (electric current-time, IT) stability test result of the chlorine evolution reaction composite electrode material prepared in Example 1. DETAILED DESCRIPTION
[0031] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0032] In the following embodiments: The commercially available titanium fiber felt is sold by Titanium New Energy Company, with specifications of 100 mm×100 mm×0.4 mm; the commercial DSA electrode specifications are "Yi Wanlin" model ywl-251 electrodes, with specifications of 10 mm×15 mm×1 mm.
[0033] Example 1 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), melamine and polyformaldehyde are mixed in a molar ratio of 1:2 (wherein melamine is 1 mmol and polyformaldehyde is 2 mmol), and then 20 mL of dimethyl sulfoxide is added, and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 5 mg of ruthenium chloride, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0034] The microscopic morphology of the chlorine evolution reaction composite electrode material prepared in this embodiment was observed using a scanning electron microscope and a transmission electron microscope. The results are as follows: Figure 1 As shown. Combined Figure 1 As can be seen from the SEM image of (a), the composite electrode material for chlorine evolution reaction is arranged alternately in a fibrous manner; Figure 1 No obvious nanoparticle agglomeration was observed in the TEM image of (b), which showed good uniformity, which helps to improve the reaction activity, stability and service life of the electrode.
[0035] Example 2 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), melamine and polyformaldehyde are mixed in a molar ratio of 1:4 (wherein melamine is 1 mmol and polyformaldehyde is 4 mmol), and then 20 mL of dimethyl sulfoxide is added, and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 5 mg of ruthenium chloride, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 hour, thereby obtaining a chlorine evolution reaction composite electrode material.
[0036] Example 3 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), melamine and polyformaldehyde are mixed in a molar ratio of 1:2 (wherein melamine is 1 mmol and polyformaldehyde is 2 mmol), and then 20 mL of dimethyl sulfoxide is added, and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 30 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 5 mg of ruthenium chloride, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 hour, thereby obtaining a chlorine evolution reaction composite electrode material.
[0037] Example 4 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), melamine and polyformaldehyde are mixed in a molar ratio of 1:2 (wherein melamine is 1 mmol and polyformaldehyde is 2 mmol), and then 20 mL of dimethyl sulfoxide is added, and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 5 mg of ruthenium chloride, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 1.5 % for 400 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0038] Example 5 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), urea and polyoxymethylene are mixed in a molar ratio of 1:2 (wherein urea is 60 mmol and polyoxymethylene is 120 mmol), and then 20 mL of acetonitrile is added and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 100° C. for 24 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 800°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 2 mg of ruthenium nitrate, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 300°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 4 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0039] Example 6 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), melamine and polyformaldehyde are mixed in a molar ratio of 1:2 (wherein melamine is 1 mmol and polyformaldehyde is 2 mmol), and then 20 mL of N,N-dimethylacetamide is added, and stirred evenly to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 1000°C at a heating rate of 5°C / min and keeping the temperature for 1 h to obtain a defective electrode material; Step (4), weigh 6 mg of ruthenium oxalate, add it to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 1.5 % for 400 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0040] Example 7 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), mixing a nitrogen source and polyformaldehyde in a molar ratio of 1:2 (wherein the nitrogen source is 0.5 mmol melamine and 0.5 mmol urea, and the polyformaldehyde is 2 mmol), then adding 10 mL dimethyl sulfoxide and 10 mL acetonitrile, stirring evenly, to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 2.5 mg of ruthenium chloride and 2.5 mg of ruthenium nitrate, add them to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0041] Example 8 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), mixing a nitrogen source and polyformaldehyde in a molar ratio of 1:5 (wherein the nitrogen source is 0.5 mmol melamine and 0.5 mmol urea, and the polyformaldehyde is 2 mmol), then adding 10 mL dimethyl sulfoxide and 10 mL acetonitrile, stirring evenly, to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 200° C. for 48 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a defective electrode material; Step (4), weigh 2.5 mg of ruthenium chloride and 2.5 mg of ruthenium nitrate, add them to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0042] Example 9 The preparation method of the composite electrode material for chlorine evolution reaction comprises the following steps: Step (1), mixing a nitrogen source and polyformaldehyde in a molar ratio of 1:3.5 (wherein the nitrogen source is 0.5 mmol melamine and 0.5 mmol urea, and the polyformaldehyde is 3.5 mmol), then adding 10 mL dimethyl sulfoxide and 10 mL acetonitrile, stirring evenly, to prepare a mixed solution; Step (2), immersing the commercially available titanium fiber felt in the mixed solution, and heating it in an oven at 150° C. for 35 h, to obtain a coated titanium substrate with the surface coated with gel; Step (3), under nitrogen protection, heating the coated titanium substrate to 900°C at a heating rate of 5°C / min and keeping the temperature for 2 h to obtain a defective electrode material; Step (4), weigh 2.5 mg of ruthenium chloride and 2.5 mg of ruthenium nitrate, add them to 20 mL of water and prepare a deposition solution, immerse the defective electrode material in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 1.5 % for 300 s to obtain a coating electrode material. Step (5), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 400°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 2.5 h, thereby obtaining a chlorine evolution reaction composite electrode material.
[0043] Comparative Example 1 The composite electrode material of this comparative example does not adopt the process of manufacturing nitrogen-oxygen double defects, and the steps are as follows: Step (1), under nitrogen protection, heating the commercially available titanium fiber felt to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 h to obtain a heat-treated titanium fiber felt; Step (2), weigh 5 mg of ruthenium chloride, add it to 20 mL of water and prepare a deposition solution, immerse the heat-treated titanium fiber felt in the deposition solution, and 2 Ruthenium was deposited by cyclic voltammetry electrodeposition at a current density of 200 s to obtain a coating electrode material. Step (3), placing the coated electrode material in a vacuum drying oven to dry overnight, and then heating to 500°C at a heating rate of 5°C / min in an oxygen atmosphere and keeping the temperature for 1 hour to obtain a composite electrode material.
[0044] The application performance of the chlorine evolution reaction composite electrode materials prepared in Examples 1-4, the composite electrode materials prepared in Comparative Example 1, and the commercial DSA electrode were tested by linear sweep voltammetry. The test adopted a standard three-electrode system, with the chlorine evolution reaction composite electrode materials prepared in Examples 1-4 and the DSA electrode as working electrodes (anodes), the counter electrode was a graphite rod electrode, the reference electrode was an Ag / AgCl electrode, and the electrolyte was 4 M NaCl (PH=2). The corresponding results are shown in FIG. Figure 2 (a). According to Figure 2 (a) LSV curve results for 10 mA cm -2 The corresponding potential V(vs)RHE under the current density is Figure 2(b), and then according to the formula: overpotential = V-1.36 V, the corresponding result can be obtained, where 1.36 V is the standard electrode potential for chloride ion oxidation. From the results, it can be seen that the chlorine evolution potential of Examples 1-3 is significantly lower than that of the commercial DSA electrode, and although the overpotential of Example 4 is slightly lower than that of the commercial DSA electrode at a low current density, it is still higher at a high current density (200-400 mA cm -2 ) has a lower overpotential than commercial DSA electrodes, which may save more power in industrial conditions. The commercial DSA electrode can reach 10 mA / cm at an overpotential of 122 mV. 2 The current density of Example 1 can reach the above current density with an overpotential of only 65.0 mV, which is significantly lower than the overpotential of the commercial DSA electrode; correspondingly, Example 2 can reach 10 mA / cm with an overpotential of only 83.6 mV. 2 The current density of Example 3 is 105.6 mV. The current density of Example 4 is 123.6 mV, which is basically consistent with the test results of the commercial DSA electrode. Under the same conditions, the overpotential of Comparative Example 1 is 161.6 mV, which is not as good as the commercial DSA electrode. In addition, from the overall development of each group of LSV curves, the chlorine evolution reaction composite electrode materials of Examples 1-4 are better than the commercial DSA electrode, while the performance of the composite electrode material of Comparative Example 1 is the worst. The above results show that the method of manufacturing nitrogen and oxygen double defects in the present invention can meet the activity requirements of the chlorine evolution reaction at extremely low precious metal content. Example 1 is the best embodiment. Using the chronoamperometric test mode in the Shanghai Chenhua electrochemical workstation, at 10 mA / cm 2 The stability test was carried out at a current density of Figure 3 As shown; the figure shows that its stable time is close to 350 h, indicating that the chlorine evolution reaction composite electrode material has good stability.
[0045] In summary, the present invention provides a simple and feasible preparation route, wherein a mixed solution containing a nitrogen source and polyformaldehyde is used to treat a titanium substrate, a gel layer is coated on the surface, and then calcined in an oxygen-free environment, and nitrogen and oxygen double defects are created on the surface of the titanium substrate to anchor the electrodeposited active metal, and finally calcined in an aerobic environment to prepare a chlorine evolution reaction composite electrode material. The reaction activity of the electrode is maintained at an extremely low content of precious metals. Due to the good adhesion and stability of the active metal, there is no need to form a uniform, dense, and continuous active metal layer, which overcomes the defect of large active metal usage in existing electrodes, and has good application prospects as an electrode material in electrolytic chlorine evolution reactions.
[0046] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a chlorine evolution reaction composite electrode material, characterized in that: The steps include: Step (1), mixing a nitrogen source, polyoxymethylene and an organic solvent to prepare a mixed solution; Step (2), immersing the titanium substrate in the mixed solution and performing heat treatment, and obtaining a coated titanium substrate after completion; Step (3), calcining the coated titanium substrate under an inert atmosphere to obtain a defective electrode material; Step (4), depositing active metal in the defective electrode material by electrodeposition to obtain a coating electrode material; Step (5), calcining the coated electrode material in an oxygen atmosphere to obtain a chlorine evolution reaction composite electrode material; In step (1), the nitrogen source includes at least one of melamine, urea, and amino acid; the organic solvent includes at least one of dimethyl sulfoxide, acetonitrile, and N,N-dimethylacetamide; the molar ratio of the nitrogen source to polyformaldehyde is 1:2-5, and the concentration of the nitrogen source in the mixed solution is 0.05-3 mol / L; In step (4), the electrodeposition method is as follows: an electrolyte containing a soluble active metal salt is used as a deposition liquid; the defective electrode material is immersed in the deposition liquid for electrodeposition to obtain a coating electrode material; the active metal is ruthenium; the current density of the electrodeposition is 30 mA / cm 2 , the electrodeposition time was 200 s; The electrodeposition adopts cyclic voltammetry electrodeposition method; the soluble active metal salt is ruthenium chloride; in the deposition solution, the solvent is water, and the concentration of the soluble active metal salt is 0.1-0.3 g / L.
2. The method for preparing the chlorine evolution reaction composite electrode material according to claim 1, characterized in that: In the step (2), the heat treatment temperature is 100-200°C and the heat treatment time is 24-48 hours.
3. The method for preparing the chlorine evolution reaction composite electrode material according to claim 1, characterized in that: In the step (3), the calcination temperature is 800-1000°C and the calcination time is 1-3 h.
4. The method for preparing the chlorine evolution reaction composite electrode material according to claim 1, characterized in that: In the step (5), the calcination temperature is 300-500°C and the calcination time is 1-4 h.
5. A chlorine evolution reaction composite electrode material, characterized in that: The method is prepared by the method according to any one of claims 1 to 4.
6. An application of the composite electrode material for chlorine evolution reaction as claimed in claim 5, characterized in that: As electrode material, it is used to prepare electrodes for chlorine evolution reaction.
Citation Information
Patent Citations
DSA (dimensionally stable anode) electrode and manufacturing method thereof, as well as ammonia-nitrogen detecting device and detecting method based on DSA electrode
CN103439385A
DSA electrode and preparation method and application thereof
CN113816468A
Preparing method of air-permeable chlorine-evolution electrode
CN107419292A
Preparation method and application of composite electrode for treating high-chlorine organic wastewater
CN113562812A
Preparation method and application based on nano ruthenium dioxide / carbon composite array
CN114836783A